Hubungan Kualitas Pemeriksaan Kehamilan Terhadap Kejadian Stunting Pada Anak Usia 6-23 Bulan di Indonesia (Analisis SKI 2023) - Audila, Hanna; Helda, Helda; Ronoatmodjo, Sudarto (Jurnal Epidemiologi Kesehatan Indonesia, 2025)
Stunting is still a nutritional problem and remains a major public health issue. Especially in Indonesia, the prevalence of stunting among children under two years old (toddlers) remains high, at 18.50%. The annual average rate of reduction of stunting among toddlers has been relatively slow for over the past 10 years. Therefore, optimizing stunting interventions-particularly during the first 1000 days of life is essential, including through antenatal care (ANC). This study aims to analyze the relationship between the quality of antenatal care and the incidence of stunting among children aged 6-23 months-old in Indonesia, after being controlled by the other variables, such are; sociodemographic factors, pregnancy’s health, and child’s health. This is a cross-sectional study, in which both of the exposures and the outcome were being measured at the same point of time. The data used are from the Indonesia Health Survey in 2023. There are 18.898 weighted-children aged 6-23 months-old and fulfilled the inclusion criteria. The analysis of association was conducted by cox-regression while the time-dependent methods and backward elimination were performed to control the covariate factors. Findings: Children aged 6-23 months-old in Indonesia, whose mothers receive low quality of antenatal care have a 1.23 times higher risk (aPR=1.23, 95%CI: 1.11-1.36, p-value = 0.000) of experiencing stunting, after controlling for the other covariate variables. Receiving at least four antenatal care (ANC) visits and accessing 10 cares can reduce the risk of stunting among children aged 6-23 months old in Indonesia. Keywords : Antenatal Care, ANC, Stunting, Toddlers, The Quality of ANC